SHARIA ECONOMIC ANALYSIS OF VILLAGE LAND AUCTIONS - Abdul Rahman Hadi (Universitas Muhammadiyah Surabaya, 2024)
This study aimed to determine the practice and results of analysis of village treasury land leasing through an auction process in Leran Kulon, Palan, Tuban. The perspective of Syari’ah Economic Law is based on shari’ah propositions and fiqh proposal principles, such as the fulfillment of legal requirements, etc. in judging related muamalah cases. Ijarah (leasing) contracts in the modern era continue to grow and have many models for selling leased objects, one of which is the village treasury land offering through an auction process in Leran Kulon, Palang, Tuban. In this leasing, many interested people are invited, but what makes it strange is that the winners of the leased land are just those people, this contains irregularities, whether the rental is running naturally or there is a game that aims to win a certain party. From here, the researcher must research to reveal the nature of the leasing. The research method used descriptive-qualitative, which provides an accurate description and picture of the nature and circumstances of the object under study based on shari’ah principles. While the data collection method used literature, interviews, and documentation The results of this study indicated that the leading of the village treasury land above is by Syai’ah Economic Law, except in the case of forfeited down payments if the auction winner does not pay 50% within 3 months of submitting the down payment. And this is still disputed by the Ulama.